Descoloração de azul de bromofenol utilizando peroxidase imobilizada em pó de sabugo de milho altamente ativado - Galárraga, Júlio César Vinueza [UNESP]; dos Santos, Andréa Francisco [UNESP]; Bassan, Juliana Cristina [UNESP]; Goulart, Antonio José [UNESP]; Monti, Rubens [UNESP] (My University, 2013)
The aim of the present study was to evaluate the efficacy of peroxidase immobilized on corncob powder for the discoloration of dye. Peroxidase was extracted from soybean seed coat, followed by amination of the surface of the tertiary structure. The aminated peroxidase was immobilized on highly activated corncob powder and employed for the discoloration of bromophenol blue. Amination was performed with 10 or 50 mmol.L-1 carbodiimide and 1 mol.L-1 ethylenediamine. The amount of protein in the extract was 0.235 ± 0.011 mg.mL-1 and specific peroxidase activity was 86.06 ± 1.52 μmol min-1. mg-1, using 1 mmol.L-1 ABTS as substrate. Ten mmol.L-1 and 50 mmol.L-1 aminated peroxidase retained 88 and 100% of the initial activity. Following covalent immobilization on a corncob powder-glyoxyl support, 10 and 50 mmol.L-1 aminated peroxidase retained 74 and 86% of activity, respectively. Derivatives were used for the discoloration of 0.02 mmol.L-1 bromophenol blue solution. After 30 min, 93 and 89% discoloration was achieved with the 10 mmol.L-1 and 50 mmol.L-1 derivatives, respectively. Moreover, these derivatives retained 60% of the catalytic properties when used three times. Peroxidase extracted from soybean seed coat immobilized on a low-cost corncob powder support exhibited improved thermal stability.
Bromofhenol blue discoloration using peroxidase immobilized on highly activated corncob powder
Keywords: Aminated enzymes; Corncob powder; Multipoint immobilization of enzymes; Peroxidases